2016
DOI: 10.1111/ceo.12704
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trabeculectomy on the accuracy of intraocular lens calculations in patients with open‐angle glaucoma

Abstract: The intraocular lens power prediction accuracy was lower in the CAT and CCT groups than in the OC group. The prediction error was greater in the CAT group than in the OC group, and the direction of the prediction error tended to be towards myopia in the CCT group. The SRK II formula may be more accurate in predicting residual refractive error in the CAT and CCT groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 24 publications
4
16
0
Order By: Relevance
“…It means that phacotrabeculectomy was effective not only for IOP control but also for stable refractive outcomes. Previous studies reported that myopic shift occurs after phacotrabeculectomy compared to phacoemulsi cation alone [11,[23][24][25]. A decreased ACD after trabeculectomy causes a myopic shift, and a decreased AL after trabeculectomy causes a hyperopic shift, conversely.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…It means that phacotrabeculectomy was effective not only for IOP control but also for stable refractive outcomes. Previous studies reported that myopic shift occurs after phacotrabeculectomy compared to phacoemulsi cation alone [11,[23][24][25]. A decreased ACD after trabeculectomy causes a myopic shift, and a decreased AL after trabeculectomy causes a hyperopic shift, conversely.…”
Section: Discussionmentioning
confidence: 97%
“…Most of the studies that focused the refractive outcomes of phacotrabeculectomy analyzed only shortterm refractive outcomes less than 6 months [11,18,[22][23][24][25], and one study reported by Chung et al [12] had a limitation that the follow-up period of the control group was average of 4.81 months. Therefore, the present study is clinically signi cant because we analyzed long-term refractive outcomes of phacotrabeculectomy up to 24 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the calculations for IOL power improve due to the development of preoperative evaluations and surgical techniques, refractive errors are becoming more predictable [22,23]. There is increasing interest in reducing prediction errors after phacotrabeculectomy because trabeculectomy can affect refractive errors after phacoemulsi cation.…”
Section: Introductionmentioning
confidence: 99%